Group guidance counseling using mind-mapping techniques to increase understanding of interests and talents to determine student career decisions - Alvinata, Ericca Putri; Hidayatullah, Rizky; Hendar, Kus (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Interests and talents are important aspects that determine the increase in student competence, including ability in career decisions. This research aims to analyze the effect of group guidance using mind mapping techniques to increase students' understanding of interests and talents to determine career decisions for class X students at State Vocational High School 3 Metro. This research uses a quantitative approach, real/pure experimental design (true-experimental design), by type of research pretest-posttest control group design. This research instrument uses a scale of interests, talents, and career decisions. Data were collected using a questionnaire tested for validity and reliability and analyzed using SPSS with normality, homogeneity, and t-test pair. The validity test results showed that all 19 questionnaire items are declared valid with an r valuecount ranging from 0.363 to 0.694, which is greater than rtable 0.349. Meanwhile, for reliability, it is said to be reliable because of the score Cronbach’s Alpha 0.874 > 0.60. The research results showed a significant difference in students' understanding of interests and talents before and after being given group guidance using techniques of mind mapping (p < 0.05). The experimental group experienced an increase in the average score from 69.90 to 80.20, with a t-value of 6.386 and a p-value of 0.000, indicating a significant effect. As for the significant differences between pretest and posttest in the experimental group with values themselves = 0.000 < 0.05. This proves that group guidance with mind-mapping techniques effectively increases understanding of students' interests and talents.